Efficacy and Safety of Bimagrumab in Sporadic Inclusion Body Myositis: Long-term Extension of RESILIENT. (23rd March 2021) - Amato, Anthony A.; Hanna, Michael G.; Machado, Pedro M.; Badrising, Umesh A.; Chinoy, Hector; Benveniste, Olivier; Karanam, Ananda Krishna; Wu, Min; Tankó, László B.; Schubert-Tennigkeit, Agnes Annette; Papanicolaou, Dimitris A.; Lloyd, Thomas E.; et al.
Abstract : Objective: To assess long-term (2 years) effects of bimagrumab in participants with sporadic inclusion body myositis (sIBM). Methods: Participants (aged 36–85 years) who completed the core study (RESILIENT [Efficacy and Safety of Bimagrumab/BYM338 at 52 Weeks on Physical Function, Muscle Strength, Mobility in sIBM Patients]) were invited to join an extension study. Individuals continued on the same treatment as in the core study (10 mg/kg, 3 mg/kg, 1 mg/kg bimagrumab or matching placebo administered as IV infusions every 4 weeks). The co–primary outcome measures were 6-minute walk distance (6MWD) and safety. Results: Between November 2015 and February 2017, 211 participants entered double-blind placebo-controlled period of the extension study. Mean change in 6MWD from baseline was highly variable across treatment groups, but indicated progressive deterioration from weeks 24–104 in all treatment groups. Overall, 91.0% (n = 142) of participants in the pooled bimagrumab group and 89.1% (n = 49) in the placebo group had ≥1 treatment-emergent adverse event (AE). Falls were slightly higher in the bimagrumab 3 mg/kg group vs 10 mg/kg, 1 mg/kg, and placebo groups (69.2% [n = 36 of 52] vs 56.6% [n = 30 of 53], 58.8% [n = 30 of 51], and 61.8% [n = 34 of 55], respectively). The most frequently reported AEs in the pooled bimagrumab group were diarrhea 14.7% (n = 23), involuntary muscle contractions 9.6% (n = 15), and rash 5.1% (n = 8). Incidence of serious AEs was comparable between the pooled bimagrumab and the placebo group (18.6% [n = 29] vs 14.5% [n = 8], respectively). Conclusion: Extended treatment with bimagrumab up to 2 years produced a good safety profile and was well-tolerated, but did not provide clinical benefits in terms of improvement in mobility. The extension study was terminated early due to core study not meeting its primary endpoint. Clinical Trial Registration: Clinicaltrials.gov identifier NCT02573467. Classification of Evidence: This study provides Class IV evidence that for patients with sIBM, long-term treatment with bimagrumab was safe, well-tolerated, and did not provide meaningful functional benefit. The study is rated Class IV because of the open-label design of extension treatment period 2.